2012
DOI: 10.1074/jbc.m111.338079
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Multidimensional Regulation of Plasminogen Activator Inhibitor Type 1 Expression by Transforming Growth Factor Type β and Epidermal Growth Factor

Abstract: Background: TGF␤ and EGF co-regulate important cellular responses, including proliferation, EMT, and PAI-1 expression. Results: TGF␤ and EGF synergistically stimulate PAI-1 transcription through Smads and AP-1 combined with mRNA stabilization. Conclusion: TGF␤ and EGF coordinate multiple cellular responses to rapidly achieve large increases in PAI-1 expression. Significance: Synergism increases the sensitivity, precision, rapidity, and range of change in specific gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Accordingly, Smad2/3 appeared to localize more readily in the nuclei of β1 integrin–deficient 4T1 cells (Figure 4B), which significantly enhanced their Smad3/4 transcriptional activity as compared with that in parental 4T1 cells (Figure 4C). Of interest, we observed that PAI-1 transcripts were similarly induced by TGF-β in both 4T1 derivatives (Figure 4D), suggesting involvement of noncanonical TGF-β in mediating this response (Song et al. , 2012).…”
Section: Resultsmentioning
confidence: 69%
“…Accordingly, Smad2/3 appeared to localize more readily in the nuclei of β1 integrin–deficient 4T1 cells (Figure 4B), which significantly enhanced their Smad3/4 transcriptional activity as compared with that in parental 4T1 cells (Figure 4C). Of interest, we observed that PAI-1 transcripts were similarly induced by TGF-β in both 4T1 derivatives (Figure 4D), suggesting involvement of noncanonical TGF-β in mediating this response (Song et al. , 2012).…”
Section: Resultsmentioning
confidence: 69%
“… 50 This reporter system is often used to test the transcriptional activity of TGF-β signaling. 51 , 52 , 53 , 54 , 55 …”
Section: Resultsmentioning
confidence: 99%
“…Methods for labeling and purifying newly synthesized RNA amenable to high-throughput downstream analyses have been employed in a variety of eukaryotes using either 4-thiouracil (4tU) or 4-thiouridine (4sU) [22], [24], [28], [29], [30], [31], [32], [33], [34], [35]. Incorporation of 4tU requires the activity of uracil phosphoribosyltransferase (UPRT), a key enzyme in the pyrimidine salvage pathway for recycling uracil to uridine monophosphate (UMP).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach is to biosynthetically label newly synthesized RNA with 4-thiouracil or 4-thiouridine, which are readily incorporated and do not impact message stability (reviewed in [28]). Thiol-specific biotinylation, followed by streptavidin-coated magnetic bead separation, enables total RNA to be separated into pools of pre-existing and newly synthesized (thiolated) RNA that are amenable to transcriptome-level downstream applications such as microarrays or RNA-seq [22], [24], [28], [29], [30], [31], [32], [33], [34], [35]. In addition to providing a means to identify transcriptionally activated genes, global RNA half-lives can be determined, capitalizing on the fact that newly synthesized RNA and pre-existing RNA pools sum to the total RNA pool.…”
Section: Introductionmentioning
confidence: 99%